Antibacterial Activity of Extracts of Pinus Wallachiana, Pinus Roxburgii and Cedrus Deodara Resins Against Some Common Pathogenic Bacteria - Muhammad Kashif, Muhammad Azam Khan, Mumtaz Hussain, Sajad Ali, Asad Ullah, Fahim Ullah, Sajjad Hussain, Nawazish Ahmad, Aitemad Hussain Mian, Ijaz Ali Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
The current research was conducted in the department of chemistry at Microbiology lab, Govt Collage Madyan, District Swat Khyber Pakhtunkhwa, Pakistan. The aim of the current study was to determine the anti−bacterial activity of different resins extracts of Pinus roxburgii, wallachiana and Cedrus deodara against Salmonella typhi, Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli by Disc diffusion method. The highest zone of inhibition was shown by methanolic extract of Cedrus deodara against S. aureus (19.6 mm) S. typhi (17 mm), E. coli (19.25 mm), and P. aeruginosa (15 mm) followed by ethanolic extract of the same plants against S. aureus (18.8 mm), S. typhi (19.33 mm), E. coli (18.1 mm), and P. aeruginosa (18.33 mm) followed by Acetone extracts of Cedrus deodara showed the maximum zone of inhibition against S. aureus (17 mm), E. coli (16.5 mm), S. typhi (16.33 mm), and P. aeruginosa (14.33 mm) followed by carbon tetrachloride extracts of Cedrus deodara against S. aureus (16.9 mm), S. typhi (16.5 mm), E. coli (12 mm), and P. aeruginosa (13.76 mm). The current study concluded that the methanolic extract of Cedrus deodara exhibit maximum anti-biogram against the test strains. Keywords: Antibacterial Activity; Pinus wallachiana, Pinus roxburgii; Cedrus deodara; common pathogenic Bacteria